Designing the open-badges guideline based on the fuzzy Delphi method - Hajar Halili, Siti; Mohsin, Norharyanti; Zainuddin, Zamzami; Othman, Juliana; Sulaiman, Shukri (Edelweiss Applied Science and Technology, 2024)
This study aims to obtain expert consensus on the appropriate elements of open badge learning guidelines. The Fuzzy Delphi Method (FDM) was used to reach a consensus from 20 experts with different backgrounds. These guidelines were designed and developed based on the Fuzzy Delphi Method (FDM) as well as the integration of the ASSURE instructional design model by Heinich, Molenda, and Russell (1993). The guidelines were evaluated by selected experts using several criteria, and data were collected through questionnaires. Based on the results of the study, all items meet the requirements in the number of three fuzzy triangles and pass the de-fuzzing process (more than Alpha α – cut-off value 0.5). Therefore, the findings of the study show that the experts agree that this module is suitable to be implemented according to the six themes set. The findings highlight key constructs for OBL guideline development included several key constructs related to OBL guideline content, state guideline objectives, method, media/tool, and material selection, as well as recommendations for use and participation based on the ASSURE instructional design model. Further research can incorporate insights from fields such as psychology, sociology, and educational policy. The focus should be on technical aspects and use qualitative and quantitative methods to ensure that all students, regardless of background, receive fair qualifications and recognition.